ASEAN's external agreements law, practice and the quest for collective action - Cremona, Marise; Kleimann, David; Larik, Joris; Lee, Rena (Lawyer); Vennesson, Pascal (Cambridge, United Kingdom Cambridge University Press, 2015)
"ASEAN is coming of age as an international actor and international treaty-maker. To date, more than 200 external agreements and other instruments have been concluded in the name of ASEAN. This book provides the first systematic account of the legal framework governing ASEAN's burgeoning external relations practice. It focuses in depth on ASEAN's wide-ranging mandate to promote its values and principles in the wider region and beyond, as well as the highly intergovernmental, and at times haphazard, handling of the bloc's relations with the outside world. Furthermore, it reveals that there are two basic meanings of ASEAN in its international dealings, which have important implications under international law: ASEAN as an international organization with its own legal personality and ASEAN as the collectivity of its Member States. This timely, thoughtful book is a valuable resource for practitioners and scholars of international law, ASEAN law, international relations, regional integration and governance"--Provided by publisher.
Machine generated contents note: General editors' preface; 1. Introduction; 2. The legal and institutional framework for ASEAN external agreements: the centrality of ASEAN; 3. An inventory and typology of ASEAN external instruments: overview and trends; 4. ASEAN as a contracting party; 5. Beyond market access? The anatomy of ASEAN's preferential trade agreements; 6. A regional strategy: a typology of ASEAN partnership and cooperation agreements; 7. Between great power rivalries and supranationality: ASEAN external instruments and regional hedging strategies; Executive summary; Appendices; Index.
Includes bibliographical references and index.
Keywords: ASEAN; Southeast Asia -- Commercial treaties; Southeast Asia -- Foreign economic relations